Extracellular Vesicle Proteomes Shed Light on the Evolutionary, Interactive, and Functional Divergence of Their Biogenesis Mechanisms - Lim, Hyobin Julianne; Yoon, Haejin; Kim, Hyeyeon; Kang, Yun-Won; Kim, Ji-Eun; Kim, Oh Youn; Lee, Eun-Young; Twizere, Jean-Claude; Rak, Janusz; Kim, Dae-Kyum (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) are membranous structures containing bioactive molecules, secreted by most cells into the extracellular environment. EVs are classified by their biogenesis mechanisms into two major subtypes: ectosomes (enriched in large EVs; lEVs), budding directly from the plasma membrane, which is common in both prokaryotes and eukaryotes, and exosomes (enriched in small EVs; sEVs) generated through the multivesicular bodies via the endomembrane system, which is unique to eukaryotes. Even though recent proteomic analyses have identified key proteins of EV subtypes, there has been no systematic analysis so far to support the validity and utility of current separation methods, largely dependent on physical properties such as vesicular size. Here, we classified human EV proteomic datasets into two main categories based on distinct centrifugation protocols commonly used for isolating sEV or lEV fractions. We found characteristic evolutionary conservation profiles of sEV and lEV proteins linked to their biogenesis origins, suggesting that the evolutionary trajectory of vesicular proteins may result in a membership bias towards specific EV subtypes. Protein-protein interaction network analysis showed that vesicular proteins formed distinct clusters with proteins in the same fraction, providing evidence for the existence of EV subtype-specific recruiters. Moreover, we identified functional modules enriched in each fraction, including multivesicular body sorting for sEV, and mitochondria cellular respiration for lEV proteins. Our analysis successfully captured novel features of EVs embedded in heterogeneous proteomics studies and suggests specific protein markers and signatures to be used as quality controllers in the isolation procedure for subtype-enriched fractions.